2004
DOI: 10.1080/02713680490503741
|View full text |Cite
|
Sign up to set email alerts
|

HLA expression in choroidal melanomas: Correlation with clinicopathological features

Abstract: HLA class I antigen and beta 2 microglobulin are negative in melanomas with no extrascleral extension and liver metastases and weak in melanomas with extrascleral extension and are positive in melanomas with liver metastases. HLA expression is independent of the conventional markers in uveal melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…AP-1, a dimeric complex consisting of proteins encoded by the Jun and Fos gene families, is a transcription factor induced by a variety of signals, including those eliciting proliferation, differentiation, and programmed cell death (apoptosis). 18 In another dimension of the current study, it is of interest to know whether the differential expression of these proteins (IGF-1R, c-Fos, and c-Jun) would possibly classify uveal melanomas into two groups as shown earlier 19 (class I melanomas with favorable outcomes had decreased to absent human leukocyte antigen and beta 2 microglobulin, and class II melanomas with liver metastasis had strong expression of HLA and β 2 m). Recently, consistent with our findings, the Harbour et al 20 group has classified uveal melanomas into two groups, class 1 (low grade), and class 2 (high grade), based on the gene expression profile, which could strongly predict metastatic death in uveal melanoma patients.…”
Section: Introductionmentioning
confidence: 93%
“…AP-1, a dimeric complex consisting of proteins encoded by the Jun and Fos gene families, is a transcription factor induced by a variety of signals, including those eliciting proliferation, differentiation, and programmed cell death (apoptosis). 18 In another dimension of the current study, it is of interest to know whether the differential expression of these proteins (IGF-1R, c-Fos, and c-Jun) would possibly classify uveal melanomas into two groups as shown earlier 19 (class I melanomas with favorable outcomes had decreased to absent human leukocyte antigen and beta 2 microglobulin, and class II melanomas with liver metastasis had strong expression of HLA and β 2 m). Recently, consistent with our findings, the Harbour et al 20 group has classified uveal melanomas into two groups, class 1 (low grade), and class 2 (high grade), based on the gene expression profile, which could strongly predict metastatic death in uveal melanoma patients.…”
Section: Introductionmentioning
confidence: 93%
“…In addition to chromosome 3, aberrations in chromosomes 1 and 8 also have been studied in UM [28][29][30]. Abnormalities in the HLA class I, β2-m, and HLA class II antigens have been reported in UM by an Indian study group [31]. Another study from India [32] highlights the significance of antigen processing molecules in MHC class I expression in UM.…”
Section: Or • Disomy 3 and 8 • Monosomy 3 And 8q Gainmentioning
confidence: 99%
“…The histopathologic features predicting prognosis of uveal melanoma include tumor cell type, mitotic activity, mean diameter of ten largest nucleoli, microvascular density (MVD), extravascular matrix patterns, tumor-infiltrating lymphocytes, tumor-infiltrating macrophages, insulin-like growth factor-1 receptor (IGF-1R), and human leukocyte antigen (HLA) Class I expression. [ 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 107 108 109 110 111 112 113 ]…”
Section: Histopathological Featuresmentioning
confidence: 99%
“…[ 109 110 111 ] However, some studies have found no association between HLA expression and melanoma-related mortality. [ 112 ]…”
Section: Histopathological Featuresmentioning
confidence: 99%